PERANAN PROGRAM-PROGRAM MASYARAKAT SENI PERTUNJUKAN INDONESIA (MSPI) DALAM MEMARTABATKAN SENI TRADISIONAL DI KALANGAN MASYARAKAT INDONESIA - Widyaratnadewi, Jeniri Amir (Universiti Malaysia Sarawak, (UNIMAS), 2006)
This study focuses on the effectiveness of the programs run by MSPI (Masyarakat Seni Pertunjukan Indonesia). The use of survey forms and interviews in this study is also to examine MSPI's functions, challenges and limitations in developing the traditional arts. This research finds that traditional arts are entrenched in mutual well-being and the MSPI programs are proven to be the link between the arts and the whole community